Correction: Communication interventions for medically unexplained symptom conditions in general practice: A systematic review and meta-analysis of randomised controlled trials. - Ailish Katherine Byrne; Arabella Scantlebury; Katherine Jones; Laura Doherty; David J Torgerson (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0277538.].